A Chat with Patricia Leavy on “Re/Invention: Methods of Social Fiction” by Patricia Leavy (2023) - Flemming, Christina (Art/Research International)

(untitled) (University of Alberta, 2023)
Within this conversation, Patricia Leavy discusses her new book Re/Invention: Methods of Social Fiction. As a leading artful scholar, Leavy shines a light on the slippage between fiction and nonfiction, and the long history of merging scholarship with the literary arts. Within the paradigm of arts-based research, Leavy views social fiction as a method. She speaks about how crafting academic fiction allows for research to become both an act of discovery and a pathway toward personal healing. Christina Flemming is delighted to hear more about Leavy’s daily writing practice, her thoughts on writing as rewriting, and the metaphorical blender that is required to take one’s lived experiences and transform them into academic fiction. You can learn more about Re/Invention: Methods of Social Fiction via the Guilford Press website. To read more about Patricia Leavy, visit her website: https://patricialeavy.com/